2010
DOI: 10.3109/0284186x.2010.530689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of symptom burden on health related quality of life of cancer survivors in a Danish cancer rehabilitation program: A longitudinal study

Abstract: Introduction . Little research has been conducted on the effect of self-reported rating of symptom severity on quality of life (QoL) among cancer survivors. The aim of the study was to examine the prevalence of symptoms and whether information about self-reported symptom severity adds value to QoL measurements. Material and methods . A questionnaire including the EORTC QLQ-C30 and an empirically derived symptom check-list was completed by 2 486 cancer survivors participating in a rehabilitation program at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 20 publications
5
33
1
Order By: Relevance
“…12 months follow-up, QOL decreased for patients with prostate-, lung-, cervix-or ovary cancer [33]. There were no differences regarding anxiety, depression or HRQOL at baseline for those who completed all four assessments compared to those 50 patients who discontinued.…”
Section: Subscalesmentioning
confidence: 46%
“…12 months follow-up, QOL decreased for patients with prostate-, lung-, cervix-or ovary cancer [33]. There were no differences regarding anxiety, depression or HRQOL at baseline for those who completed all four assessments compared to those 50 patients who discontinued.…”
Section: Subscalesmentioning
confidence: 46%
“…Longitudinal studies have confirmed fatigue as the most prevalent physical effect after breast cancer treatment 40,44,45 . However, these sa women reported that pain and nerve damage were also largely responsible for a decline in quality of life that limited their ability to function at their previous jobs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Many patients who have undergone cancer treatment can be limited in their activities of daily life by the symptoms caused by their disease or its treatment 1,2 . Cancer rehabilitation is a process that assists the individual's physical, social, psychological, and vocational functioning within their limits 1 .…”
Section: Introductionmentioning
confidence: 99%